(untitled) (Revista Iberoamericana de Bioética, 2026)
In recent years, significant ethical questions have emerged regarding substance use and care policies, making it necessary to conduct a critical analysis of the conflicts identified. The aim of this article is to explore the bioethical dilemmas associated with the field of drug demand reduction. In this study, the various ethical conflicts were grouped into several categories—substance use and autonomy, legalisation versus prohibition, social responsibility, prevention, treatment, and harm reduction—and analysed through the lens of diverse ethical theories. This preliminary review highlights the urgent need to address the dilemmas arising at all levels of this issue through a multidisciplinary approach that encompasses public awareness‑raising, the training of health professionals, the development of public policies and care programs, and the approval of legal initiatives that contribute to safeguarding the health of people who use psychoactive substances.